BID links ferroptosis to mitochondrial cell death pathways - Neitemeier, Sandra; Oppermann, Sina (Redox Biology, 2017)
Ferroptosis has been defined as an oxidative and iron-dependent pathway of regulated cell death that is distinct from caspase-dependent apoptosis and established pathways of death receptor-mediated regulated necrosis. While emerging evidence linked features of ferroptosis induced e.g. by erastin-mediated inhibition of the Xc- system or inhibition of glutathione peroxidase 4 (Gpx4) to an increasing number of oxidative cell death paradigms in cancer cells, neurons or kidney cells, the biochemical pathways of oxidative cell death remained largely unclear. In particular, the role of mitochondrial damage in paradigms of ferroptosis needs further investigation.